Simulasi Komunikasi V2V (Vehicle-to-vehicle) Dari Website Peta Riil Sebagai Pembentukan Skenario Daerah BSD, Tangerang Selatan Menggunakan Simulator SUMO dan Omnet++ - Riefky Rakadiansyah; Suwasti Broto (FAKULTAS TEKNIK UNIVERSITAS BUDI LUHUR, 2021)
Abstract in ENGLISH The purpose of this research is to optimize the movement of vehicles in the BSD area, South Tangerang which has a density of vehicles at certain hours. In this study, data on vehicle density calculated manually from a smartphone application called CCTV ATCS INDONESIA from 10:11:46 WIB to 10:27:14 WIB with a total of 154 units of vehicles, from 13:00:57 to 12:00 WIB 13: 15:51 WIB with a total of 142 units of vehicles, and at 17:14:19 WIB until 17:33:14 WIB with a total of 178 units of vehicles. So we need a system that reduces density and avoids road accidents, namely VANET. Because VANET will make it easier for drivers to communicate with each other and exchange information. To achieve this communication, the AODV routing protocol takes a role in this case which will later be created in the SUMO and Omnet ++ simulators. In the SUMO simulator, the communication chats with an indicator in red every time, while in Omnet ++ it reports with a blue indicator. The results of the VANET simulation that have been run from Omnet ++ can also display the results per-node or the entire node at once. The results that can be accessed include maxspeed, sentpackets, totalDistance and others. The resulting parameters have already been defeated by the survey data conducted before the simulation was run on Omnet ++. By applying this research, the movement of each vehicle can be stabilized and does not apply to a collision.